Pemodelan Sistem Pakar Untuk Identifikasi Kerusakan Kamera Digital Single Lens Reflex (DSLR) Canon Menggunakan Metode Dempster - Shafer - Rihandiko Hari Romadhona; Suprapto Suprapto; Nurul Hidayat (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Today's digital age computer development is necessary to alleviate human work, especially the development of the world of photography. Various photographic devices that support to recieved humans have increasingly sophisticated. One is a Digital Single Lens Reflex camera (DSLR). Therefore this camera very popular by the public. But there is problem if the camera is damaged. Dempster - Shafer has been successfully applied in real-world problems and provides better solutions, where Dempster - Shafer can applied to multisensor and / or multisumbered data including data from remote sensing. Subjects in this research is the application system using Dempster - shafer method as detection medium on damage to Digital Single Lens Reflex (DSLR) camera. Collecting data in research by doing with expert. The result of this research the application system for identification of Digital Single Lens Reflex (DSLR) camera damage using Dempster - shafer method containing various symptoms, kinds of damage solution and result of detection based on knowledge base of experts or experts in Digital camera field Single Lens Reflex (DSLR). From the test cases that have been done the results accuracy level of testing is 90% indicating the system works well in accordance with the method Dempster - Shafer.